UTILIZAÇÃO DE ISOLADOS DE TRICHODERMA NATIVOS DE AQUIDAUANA PARA CONTROLE DE MACROPHOMINA PHASEOLINA. - SOARES, Rayssa da Silva; COSTA, Brenda Fernandes da; SILVA, Talísia de Souza da; BLANCO, Neder Henrique Martinez; Graichen, Felipe André Sganzerla (ANAIS DO ENIC, 2025)
-